Students' perception towards majoring in accounting: A study in Universiti Teknologi MARA (UiTM) Pahang / Ida Haryanti Mohd Noor and Rosliza Abu Bakar - Mohd Noor, Ida Haryanti; Abu Bakar, Rosliza (2013)
Human capital is one of the main resources that play significant roles in ensuring the organization achieve its objectives. They need to fulfill the criteria that have been set by the organization if they want to be in the organization. It is crucial to find employees that meet those criteria especially in accounting profession. This was due to a declining number of university students majoring in accounting programs. Prior researches show that there are many reasons contribute to a declining number of students enrolling in accounting programs. Thus. present study will focus on three factors which are personal perception. perception of important referents and perceived controls in order to better explain and affect the relationship between students' perception and their intention to major in accounting. The questionnaires were distributed to semester four and semester six students who enrolled Bachelor of Accountancy in Universiti Teknologi MARA Pahang. This research will provide valuable information and better understanding on factors that influenced their choice of majoring in accounting.